Rural slaughter and microbiological implications for the countryside consumer with cultural preferences and eating habits - BURRIEU, ANGELIKI R; PAPAGIANNI, RENA (The Indian Journal of Animal Sciences, 2014)
Rural butcher premises are small family enterprises with well defined clientele and source of products sold. As such, they are thought by their customers, and could be, as free of microorganisms of major public health importance derivingfrom contamination during mass processing of meat or meat products. In the present, investigation was attempted todiscuss the health implications from the multitude of microorganisms isolated in such enterprises. They are suggesting that these premises could be potential sources of human infection by microorganisms of public health importance due to improper handling of meat products. The small size of the enterprises contributes to mixing of meat kinds and meat products increasing the risk to public health, which is further increased by the lack of training of show owners on public health. Improvements are possible if mandatory and regular training of owners and their assistavts is practiced through a system of continuous certifioation on steps needed in minimizing the spread of potential pathogens of public health importance. Non-compliance should be followed by closure of premises, a measure protecting this type of business rather than eliminating it.